Amplitude modulation and soliton formation of an intense laser beam interacting with dense quantum plasma: Symbolic simulation analysis. Issue 8 (7th April 2020) - Das, Chinmay; Chandra, Swarniv; Ghosh, Basudev
Abstract: In this theoretical study, we investigate the amplitude modulation and envelop soliton formation in a dense plasma when such a plasma interacts with a strong laser beam. We have made use of the symbolic simulation technique to find the modulation instability of an electrostatic wave with higher orders of non‐linearity. We identified the range of wavenumber in which such non‐linearity is important. Furthermore, we have analysed the formation of envelope soliton of waves localized in space. The results obtained here will be helpful in interpreting different phenomena that arise in laser plasma interaction. The importance of the relativistic contribution of streaming particles is discussed alongside the parametric influences experienced by the plasma particles. Abstract : Electric field surface evolution on x  –  z plane at t  = 8 fs for n 0  = 10 27 / m 3, λ  = 10 −10 m, T  = 13  eV